Pengambilan Keputusan Pegawai Tidak tetap menjadi Pegawai Tetap Dengan Decission Tree - Febryantahanuji Febryantahanuji (Universitas Ivet, 2018)
Employee recruitment is something sensitive in a company. Therefore, the company which hiring an employee have to notice the factor which affect eligibility that employee to be used as a permanent employee. So, to ignore an error, a company should have a system to help them to minimalize recruitment from outsourcing employee to be a permanent employee in a company. The application decission tree C4.5 method in a employee recruitment selection can help a company for determining an employee which is eligibility with predicted as well as portend data with make tree structure which have code from result of that attribute test, using algoritma C4.5 it can get a main indicator in a employee recruitment.